TAWAKAL DAN KECEMASAN MAHASISWA PADA MATA KULIAH PRAKTIKUM - Agus Mulyana (Psympathic : Jurnal Ilmiah Psikologi, 2015)
This research was focused to get an overview of tawakal and anxiety among students who taking courses of the Rorschach test practicum at the Psychology Faculty of UIN Sunan Gunung Jati Bandung. Data were collected from 32 students by using questionnaires of tawakal and anxiety. The tawakal questionnaire used instrument made by Prapti Ningsih, consist of 53 items. Level of anxiety assessed by the Penn State Woory Questionnaire (PSWQ) developed by Meyer, Miller, Metzger, and Borkovec, which consist of 16 items. The result has shown that 4 students have high scores in both tawakal and anxiety. 18 students with high of tawakal and moderate anxiety. 6 students with high in tawakal and low anxiety. A student with moderate in tawakal and high anxiety. 3 students with a moderate score in both tawakal and anxiety.